Inhaled Triple Therapy with Extrafine Single Inhaler Versus Multiple Devices in Chronic Obstructive Pulmonary Disease (TRIPOLI): A Post-Authorization Retrospective Study - Cabrera César E; López García J; Vega Lizarazo DE; Benítez-Cano Gamonoso M; Segura Romero M; Sanchez Martín S; León Nieto MI; González-Segura Alsina D; Velasco Garrido JL (International Journal of COPD)
Eva Cabrera César,1 Javier López García,1 Daniel Enrique Vega Lizarazo,1 Miguel Benítez-Cano Gamonoso,1 Mercedes Segura Romero,1 Sara Sanchez Martín,1 Mónica I León Nieto,2 Diego González-Segura Alsina,2 José Luis Velasco Garrido1 1Pulmonology Department, Virgen de la Victoria University Hospital, Málaga, Spain; 2Chiesi España, Barcelona, SpainCorrespondence: José Luis Velasco Garrido, Pulmonology Department, Virgen de la Victoria University Hospital, Campus de Teatinos s/N, Puerto de la Torre, Málaga, 29010, Spain, Email jlvelascogarrido@hotmail.comBackground: Triple therapy significantly enhances both clinical and functional outcomes in patients with uncontrolled chronic obstructive pulmonary disease (COPD), even when they are already receiving treatment. However, it is often prescribed with multiple inhalers, which can affect adherence to treatment. The evidence on the effectiveness of extrafine single inhaler triple therapy (efSITT) compared to multiple inhalers triple therapy (MITT) in patients with moderate-to-severe COPD in the real-world setting is limited.Methods: TRIPOLI was a unicentric retrospective observational study that compared one year of efSITT with beclomethasone dipropionate, formoterol fumarate dihydrate, and glycopyrronium with one year of MITT in terms of exacerbations, use of rescue medication, adherence, and lung function in patients with COPD.Results: A total of 71 patients were analyzed. The mean number of total and moderate exacerbations showed a significant reduction of 27.56% (p = 0.0043) and 29.56% (p = 0.0008), respectively, after efSITT. The percentage of patients with poor adherence decreased from 30.2% to 9.9% with efSITT and the proportion of patients with complete adherence increased from 55.8% to 81.7%. An improvement of 2.29% was described in mean forced expiratory volume in the first second (% pred). No differences were observed in the rate of pneumonia between the treatment with efSITT and MITT.Conclusion: The TRIPOLI study suggests that switching from MITT to efSITT might reduce exacerbations in patients with moderate-to-severe COPD, likely attributable to improved adherence in real-world settings.Keywords: chronic obstructive pulmonary disease, triple inhalation therapy, extrafine particles, medication adherence, respiratory function tests, real-world